Analisis Konten Electronic-Word of Mouth (E-WOM) yang Digunakan Akun Tiktok @Warungmamazafran12 dalam Mencapai Popularitas - Jessica Jolie; Hayu Wirati; Belinda Patresia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Technological advances have brought about dynamic changes in the word of mouth (WOM) communication process which has developed into electronic word of mouth (E-WOM). The difference lies in eWOM using the utilization of the internet and social media in the digital era. Marketing through eWOM is becoming an increasingly dominant strategy utilized by business owners in achieving their popularity on social media. Social media is now the center of attention because it is not only used as a means of entertainment but also as a place to do business so that business owners use TikTok social media to build the image and popularity of their products. The purpose of this study is to analyze the eWOM content in the TikTok account @warungmamazafran12 to achieve its popularity on TikTok social media.